A Coupling Electromechanical Cell-Based Smoothed Finite Element Method Based on Micromechanics for Dynamic Characteristics of Piezoelectric Composite Materials - Jianxiao Zheng; Zhishan Duan; Liming Zhou (Advances in Materials Science and Engineering)
Coupling electromechanical cell-based smoothed finite element method (CSFEM) with the asymptotic homogenization method (AHM) is presented to overcome the overstiffness of FEM. This method could accurately simulate the dynamic responses and electromechanical coupling effects of piezoelectric composite material (PCM) structures. Firstly, the efficient performances for active compounds of round cross-section fibers are calculated based on AHM. Secondly, in the CSFEM, electromechanical multi-physic-field FEM is coupled with gradient smoothing technique. CSFEM returns the nearly exact stiffness of continuum structures, which auto discretes the elements in complex areas more readily and thus remarkably reduces the numerical errors. Static and dynamic characteristics of four PCM structures are investigated using CSFEM with AHM. Results are compared with analytical solution and those of FEM, which proves that CSFEM with AHM is more accurate and reliable than the standard FEM when solving problems of complex structures. Additionally, CSFEM could provide results of higher accuracy even using distorted meshes. Therefore, such method is a robust tool for analyzing mechanical properties of PCM structures.